Reducing female admissions to custody: exploring the options at sentencing - Roberts, Julian V. (Criminology & criminal justice, 2017)
Although women represent a small minority of the prison population in all nations, it has long been a concern that custody is overused with respect to female offenders. Reducing the number of women in prison has therefore emerged as a policy priority in many western nations, including the United Kingdom. This article evaluates a range of sentencing strategies to reduce the number of women in prison, on the grounds that their experience of the sanction is disproportionately severe. The challenge is to achieve a reduction in women’s imprisonment without compromising the fundamental sentencing principles of equity and proportionality. Although no jurisdiction has launched a sentencing initiative with this specific aim, the international sentencing literature offers insight into the most effective methods by which reductions may be achieved. Informed by the principle of equal impact, which underpins gender-specific sentencing, we explore policy options in two principal domains: (1) statutory provisions to eliminate or restrict judicial discretion to imprison female offenders; and (2) sentencing guidelines to structure judicial discretion in gender-sensitive ways. We conclude by considering the likelihood of implementing the options.